peningkatan kualitas air menggunakan filter mangan zeolit dan karbon aktif - Jundulloh, Panglima; Winarno, Dwi Joko; Kusumastuti, Dyah Indriana; Khotimah, Siti Nurul (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Water is a chemical compound that is very important for human life and other living things. the quantity and quality of the well as a water source must meet the physical, chemical and bacteriological requirements. Therefore, proper groundwater treatment is needed to process it into clean water that meets the requirements in terms of quality and quantity so that it is suitable for use by humans. To improve water quality, you can use methods such as filtration. In this final project, water quality improvement is carried out using manganese zeolite and activated carbon filters. The result of this research is to know the efficiency of iron (Fe), manganese (Mn) and E.coli removal using this unit. The results of laboratory tests conducted by the Research and Industrial Standardization Institute of Bandar Lampung with water samples with most parameters such as Fe and Mn have met the standards of the Regulation of the Minister of Health of the Republic of Indonesia Number 32/MENKES/PER/II/2017 concerning Clean Water Quality Requirements, but the test results with E-coli bacteria parameter is 2863 per 100 ml sample which exceeds the maximum level of 0. From this study manganese zeolite and activated carbon filters are effective in reducing TDS levels by 133 and E-Coli bacteria with results of <300 Keywords: water cleaner, zeolite manganese filter and activated carbon